Psychometric properties of the Flourishing Scale in Colombian adults - Trejos-Herrera, Ana M. (2026)
Objective: To determine the psychometric properties of the Flourishing Scale (FS) in Colombian adults. Methodology: The FS scale was applied to a sample of 498 adults (19.7% men and 80.3% women), aged between 18 and 45 years. A confirmatory factor analysis was performed using the unweighted least squares method. Results: The CFA supported a single-factor structure consisting of eight items, consistent with the original theoretical model proposed by Diener et al. The model fit indices showed mixed results: χ² = 216.97; RMSEA = 0.14; GFI = 1.00; RMR = 0.0063; CFI = 1.00. Although CFI and GFI indicated optimal fit, the RMSEA value suggested a limited model fit. Reliability estimates were satisfactory, with Cronbach’s alpha and McDonald’s omega coefficients exceeding 0.70. Conclusions: The FS scale is a valid and reliable instrument to assess flourishing in the Colombian adult population.